Customer Engagement with Universities’ Social Media after COVID-19: EaP Countries Case - Chala Nina (EDP Sciences, 2021)
The current research aims at analyzing the social media activity of the universities in EaP countries. During the COVID-19 pandemic, universities had to transfer their education processes and enrollment campaigns online. University management had to introduce new tools for communication and interaction to ensure the efficacy of cooperation between the university community, students, teaching staff, and other stakeholders. In this research, the authors analyze which factors affected the dynamics and directions of customer engagement with Universities' social media and how. The authors propose a framework to reveal the role of countries’ digital environment, educational environment, and university’s SM activity in increasing ER of university stakeholders during the COVID-19 pandemic on Facebook and Instagram. The authors outline managerial proposals for universities, including analytics-based SM content creation and planning, communicating socially essential issues.